Evaluation of Operational Efficiency of Conventional and Sharia Rural Credit Banks (BPR) in Solo Raya Using Data Envelopment Analysis - Wahid Nur Hasan; Imronudin; Muhammad Sholahudin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze and compare the operational efficiency of conventional Rural Credit Banks (BPR) and Sharia Rural Credit Banks (BPRS) operating in the Solo Raya area during the period 2020 to 2024. Using the Data Envelopment Analysis (DEA) method, this study measures the technical efficiency level of each bank and identifies the main factors that affect their performance. The input variables used include total assets, operating costs, third-party funds, and employee expenses, while the output variables consist of operating income, credit/financing distribution, and net profit. The results of this study show that there are significant variations in efficiency between BPR and BPRS, with operational scale, cost discipline, and financial structure as the main determining factors. This study contributes to the literature on microbanking efficiency in Indonesia and offers empirical evidence and practical recommendations for bank management and regulators in improving operational strategies and financial sustainability.